IMPROVING SKI LEARNING OUTCOMES THROUGH MIND MAP METHOD IN CLASS VIII STUDENTS OF MTS NEGERI 4 ROKAN HULU - Murtinis Murtinis (Indonesian Journal of Basic Education, 2021)
This study aims to determine whether the mind map learning method can improve student learning outcomes of the Ayyubid dynasty material for class VIII MTs Negeri 4 Rokan Hulu students in 2020. The subjects of this study were SKI subject teachers and class VIII students of MTs Negeri 4 Rokan Hulu which consisted of 31 student. The method used is Classroom Action Research (CAR). The steps in this CAR are planning, action, observation and reflection which are carried out in two cycles. Data collection methods used were written tests, observation sheets and documentation. Meanwhile, data analysis was carried out by comparing the achievement of the value of each cycle marked by an increase in the Classical Completeness Criteria. The results of the research in cycles I and II obtained the following data: The KKM standard for SKI subjects was 70, learning outcomes were obtained from pre-cycle, cycle I to cycle II, where the average value of pre-cycle 68 increased to 74.84 in cycle I and then increased again to 80.97 in the second cycle. The learning process is said to be successful or complete if the classical learning outcomes reach 85%. From the pre-cycle before using the mind map learning method, the students' completeness was 48%. Meanwhile, the students' completeness in the first cycle was 72% and the second cycle students' completeness was 97% and 97% 85%. Thus, the application of the mind map method on the subject of Islamic Cultural History (SKI) material for the Ayyubid Dynasty in class VIII MTs Negeri 4 Rokan Hulu is said to be successful